Investigation of the Distribution of the Daytime Employed Population of Yangon, Myanmar, with and without the Impact of Work from Home - Ye Wint Aung; San San Myint (Universitas Gadjah Mada, 2021)
Work from home (WFH) has gradually become more popular since COVID-19 started its transmission in Myanmar during the first quarter of 2020. Its consequence was a re-evaluation of the culture of workplaces and a significant change has occurred to the pattern of daytime employment distribution. In this paper, the network distribution model was built with three constraints, Distribution Bias 1, 2, and 3. These biases were determined through questionnaires, survey data collections of responses from Yangonites, and geographical data of urban employment cores. These percentile biases influenced the amount of employed population per distribution times and gave rise to two results. One was the ordinary daytime employed population and another was the improved daytime employed distribution (considering WFH). These two results were compared and contrasted with coefficient of variations, t-tests, and other correlation methods to determine the effect of WFH on the daytime employed population. With survey data, it was clarified that majorities in Yangon do favor work from home as an alternative option for future employment. Subsequently, the compared results revealed that work from home significantly decreased the amount of employment distribution and the amount of such decrements were more consistent and had less variations, hence reducing cramming during daytime distribution.